Wealth-based equity in essential newborn care practices in Ethiopia: A cross-sectional study - Tadesse Guadu Delele; Lars Åke Persson; Kassahun Alemu Gelaye; Joanna Schellenberg; Seblewengel Lemma; Atkure Defar; Theodros Getachew; Girum Taye; Solomon Shiferaw; Zewditu Abdissa; Amare Tariku; Meseret Zelalem; et al. (PLoS ONE, 2025)
Background The World Health Organization has listed several newborn care practices as essential for health and survival. Reports from low-income countries, including Ethiopia, have shown inequities in these practices, but their link to place of birth remains insufficiently explored. We aimed to analyze the wealth-based equity of selected essential newborn care practices, i.e., skin-to-skin care, delayed bathing, proper cord care, and timely breastfeeding initiation, among neonates born in health facilities and homes in Ethiopia. Methods The Performance Monitoring for Action Ethiopia 2019–2020 survey was conducted in five regions, representing 90% of the country’s population, and included data on 2,493 newborns. Household wealth quintiles were derived using principal component analysis of asset ownership. We analyzed the wealth-based equity of selected essential newborn care practices for facility and home deliveries using equiplot, equity gaps, equity ratios, and concentration indices. Results Overall, skin-to-skin care and delayed bathing showed minimal inequities among babies born in health facilities. When comparing the extreme wealth groups, minor socio-economic differences were observed in delayed bathing and timely breastfeeding initiation. When wealth was treated as a continuous variable across all respondents, delayed bathing and proper cord care were more common in better-off households. For home births, the equiplots showed that all selected essential newborn care practices were more frequent among the least poor groups. While comparing the extreme wealth groups, socio-economic inequities were evident in skin-to-skin care and delayed bathing practices. When wealth was considered a continuous variable, skin-to-skin care and delayed bathing were more common among better-off households. Conclusion The coverage of selected essential newborn care practices was higher in facility deliveries. There were minimal socio-economic differences in newborn care for facility births, while inequities in skin-to-skin care and delayed bathing were prominent in home births. Initiatives should aim to enhance equity in newborn care within health facilities while promoting facility deliveries and improving newborn care practices at home to achieve equitable newborn care in Ethiopia.